2021
DOI: 10.1007/s40487-021-00156-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of Proton Pump Inhibitors on the Efficacy of Dacomitinib and Gefitinib in Patients with Advanced Non-Small Cell Lung Cancer and EGFR-Activating Mutations

Abstract: Introduction: Dacomitinib and gefitinib are irreversible epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKI) indicated for the first-line treatment of patients with advanced non-small cell lung cancer (NSCLC) and EGFR-activating mutations. Pharmacokinetic (PK) studies in healthy volunteers suggested that acid-reducing drugs such as proton pump inhibitors (PPI) decreased dacomitinib and gefitinib exposure by limiting the pH-dependent absorption. This analysis retrospectively evaluates the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…As shown in Table 1 , thirteen cohort studies [ 11 23 ] including 12259 patients with NSCLC that were treated with TKIs were included. Since one study reported two cohorts of patients taking dacomitinib or gefitinib, respectively [ 22 ], these two datasets were included independently in the meta-analysis. These studies were published between 2013 and 2021 and performed in Canada [ 11 , 12 ], Spain [ 16 ], the United States [ 18 , 22 ], Japan [ 15 , 23 ], Singapore [ 14 ], and China [ 13 , 17 , 19 – 21 ], respectively.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As shown in Table 1 , thirteen cohort studies [ 11 23 ] including 12259 patients with NSCLC that were treated with TKIs were included. Since one study reported two cohorts of patients taking dacomitinib or gefitinib, respectively [ 22 ], these two datasets were included independently in the meta-analysis. These studies were published between 2013 and 2021 and performed in Canada [ 11 , 12 ], Spain [ 16 ], the United States [ 18 , 22 ], Japan [ 15 , 23 ], Singapore [ 14 ], and China [ 13 , 17 , 19 – 21 ], respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Since one study reported two cohorts of patients taking dacomitinib or gefitinib, respectively [ 22 ], these two datasets were included independently in the meta-analysis. These studies were published between 2013 and 2021 and performed in Canada [ 11 , 12 ], Spain [ 16 ], the United States [ 18 , 22 ], Japan [ 15 , 23 ], Singapore [ 14 ], and China [ 13 , 17 , 19 – 21 ], respectively. All of the studies were retrospective cohort studies and included patients with advanced NSCLC treated with TKIs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations